2015
DOI: 10.1158/0008-5472.can-14-3167
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Resistance to the Mutant-Selective EGFR Inhibitor AZD9291 Is Associated with Increased Dependence on RAS Signaling in Preclinical Models

Abstract: Resistance to targeted EGFR inhibitors is likely to develop in EGFR mutant lung cancers. Early identification of innate or acquired resistance mechanisms to these agents is essential to direct development of future therapies. We describe the detection of heterogeneous mechanisms of resistance within populations of EGFR mutant cells (PC9 and/or NCI-H1975) with acquired resistance to current and newly developed EGFR TKIs including AZD9291. We report the detection of NRAS mutations, including a novel E63K mutatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
270
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(286 citation statements)
references
References 38 publications
13
270
2
1
Order By: Relevance
“…Preclinical studies have also identified potential resistance mechanisms. For example, cells that are resistant to osimertinib appear to have enhanced levels of phosphorylated MEK and may be particularly sensitive to combined EGFR and MEK inhibition [57,58]. The identification of heterogeneous resistance mechanisms to osimertinib has prompted the initiation of several early-phase clinical trials [59].…”
Section: Factors Influencing First-line Treatment Choice: Mechanismsmentioning
confidence: 99%
“…Preclinical studies have also identified potential resistance mechanisms. For example, cells that are resistant to osimertinib appear to have enhanced levels of phosphorylated MEK and may be particularly sensitive to combined EGFR and MEK inhibition [57,58]. The identification of heterogeneous resistance mechanisms to osimertinib has prompted the initiation of several early-phase clinical trials [59].…”
Section: Factors Influencing First-line Treatment Choice: Mechanismsmentioning
confidence: 99%
“…Eberlein and colleagues conducted a very meaningful pre-clinical study regarding the involvement of RAS-MAPK pathway in acquired resistance to third-generation TKIs (31). With a comparison across 32 populations of cell lines with acquired resistance to different EGFR-TKIs, the authors detected, as frequent mechanisms of resistance to osimertinib, NRAS missense mutations (including a novel E63K mutation) or NRAS copy number gain.…”
Section: Ras-mapk Pathway Activationmentioning
confidence: 99%
“…AZ7550 showed a comparable potency and selectivity profile similar to osimertinib, whereas AZ5104 in addition exhibited greater potency against exon 19 deletion and T790M mutants and wild-type EGFR. The first phase I dose escalation study was the AURA, made with EGFR mutated patients in progression with gefitinib or erlotinib treatment [11,[16][17][18]. The doses used were between 20 and 240 mg per day.…”
Section: Osimertinib (Azd9291)mentioning
confidence: 99%
“…The most frequent were rash, diarrhea and nausea. Since no significant difference in response to higher doses was observed, 80 mg/day is recommended until disease progression or unacceptable toxicity [16][17][18]. If it is necessary to reduce the dose, this should be done at 40 mg per day, since tablets are 40 and 80 mg. Its elimination is mainly hepatic and has not been studied in patients with renal insufficiency [16].…”
Section: Osimertinib (Azd9291)mentioning
confidence: 99%